The system of exercises for forming future university English teachers’ socio-сultural competence by means of information research project - Ю. Г. Безвін (Іноземні мови, 2016)
Abstract. Introduction. The on-line news articles of the British and American newspapers and magazines are viewed as an effective source of the latest socio-cultural information. They contain up-to-date social, cultural and linguistic data, which is essential for obtaining the socio- cultural knowledge and developing skills. The key thing in forming the socio-cultural competence of future University teachers of English is developing the system of exercises aimed at forming a set of socio-cultural skills in reading and analyzing the news articles critically, building on intercultural tolerance. One of the most effective ways to do this is to develop a system of exercises for forming socio-cultural competence by means of Information Research Project. Purpose. To develop the list of the main components of the socio-cultural competence to be formed and assessed; to specify the stages of forming socio-cultural competence in accordance with the project work stages and project activities; to give the examples of the exercises, as well as their analysis. Methods. Reviewing the scientific studies on the most efficient ways to develop the system of exercises. Results. The article describes the system of exercises for forming the socio-cultural competence of future university English teachers’ by means of Information Research Project. Conclusion. As a recap, the given system of exercises meets the requirements of the process of forming sociocultural competence effectively.